Transgender Adults' Access to College Bathrooms and Housing and the Relationship to Suicidality. Issue 10 (2nd October 2016) - Seelman, Kristie L.
ABSTRACT: Transgender and gender non-conforming people frequently experience discrimination, harassment, and marginalization across college and university campuses (Bilodeau, 2007; Finger, 2010; Rankin et al., 2010; Seelman et al., 2012). The minority stress model (Meyer, 2007) posits that experiences of discrimination often negatively impact the psychological wellbeing of minority groups. However, few scholars have examined whether college institutional climate factors—such as being denied access to bathrooms or gender-appropriate campus housing—are significantly associated with detrimental psychological outcomes for transgender people. Using the National Transgender Discrimination Survey, this study analyzes whether being denied access to these spaces is associated with lifetime suicide attempts, after controlling for interpersonal victimization by students or teachers. Findings from sequential logistic regression ( N = 2, 316) indicate that denial of access to either space had a significant relationship to suicidality, even after controlling for interpersonal victimization. This article discusses implications for higher education professionals and researchers.